Pemanfaatan Canva AI sebagai Media Pembelajaran Interaktif Bahasa Indonesia di SMA/SMK: Kajian Sistematis Literatur - JH. Fahrizal Nur Rizky (SulukAksara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The Advances in artificial intelligence (AI) technology have presented new opportunities in education, one of which is the use of Canva AI. This article aims to explore the potential, implementation, and challenges of Canva AI as an interactive Indonesian language learning medium at the high school/vocational school level. The research method used was a Systematic Literature Review (SLR), analyzing various articles, proceedings, research reports, and other relevant academic sources related to the use of Canva AI and digital media in language learning. The study results show that Canva AI features, such as Magic Write, Magic Design, Text-to-Image, and Canva Code, support teachers in designing more efficient, creative, and adaptive teaching materials, while aligning with the spirit of the Independent Curriculum. Canva AI enables the creation of multimodal content in the form of posters, infographics, presentations, and video narratives that are contextualized to students' needs. This not only makes it easier for teachers to prepare teaching materials but also encourages active student engagement through collaborative activities and project-based learning. The integration of Canva AI has also been shown to increase student motivation, interest in reading and writing, and creativity, while providing a more varied and innovative learning environment than conventional methods. However, the use of Canva AI still faces several challenges, such as the risk of over-reliance on automated output, the potential for homogeneity of work, limited teacher digital literacy, and the need for adequate technological infrastructure support. In conclusion, Canva AI plays a crucial role as a relevant, innovative, and inclusive pedagogical companion in Indonesian language learning in high schools (SMA/SMK). This study enriches the literature on digital education in Indonesia and provides recommendations for teachers and schools in optimizing AI technology to achieve creative, interactive learning that meets the demands of the 21st century.